2017
DOI: 10.1037/pla0000052
|View full text |Cite
|
Sign up to set email alerts
|

Effects of child-centered play therapy for students with highly-disruptive behavior in high-poverty schools.

Abstract: Authors examine effects of child-centered play therapy (CCPT) within a serviceresearch project. Students were referred for highly disruptive behavior by principals, with teacher input, following guidance through referral definitions and indicators provided by the authors. CCPT services were provided in high-poverty schools by counseling interns or beginning play therapists in close supervision. Findings include significant differences for treatment versus control groups and moderate to large effects from 9-ses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 39 publications
0
10
0
3
Order By: Relevance
“…The current study did not assess therapist factors, including implicit bias, that may have influenced who was offered TF-CBT compared with CCT in this study. One possible explanation for our finding may be that many trauma-exposed youth present to community mental health clinics due to disruptive behavior problems, and therapists may feel the need to meet the client where they indicate they need help (i.e., the disruptive behavior), which may influence choosing CCT over TF-CBT as a starting point (Cochran & Cochran, 2017). CCT, which focuses on utilizing empathy and positive regard to increase a child’s awareness and processing of experiences, is commonly used by therapists to decrease disruptive behavior in youth and some studies suggest it is an effective intervention for disruptive behaviors (Cochran & Cochran, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The current study did not assess therapist factors, including implicit bias, that may have influenced who was offered TF-CBT compared with CCT in this study. One possible explanation for our finding may be that many trauma-exposed youth present to community mental health clinics due to disruptive behavior problems, and therapists may feel the need to meet the client where they indicate they need help (i.e., the disruptive behavior), which may influence choosing CCT over TF-CBT as a starting point (Cochran & Cochran, 2017). CCT, which focuses on utilizing empathy and positive regard to increase a child’s awareness and processing of experiences, is commonly used by therapists to decrease disruptive behavior in youth and some studies suggest it is an effective intervention for disruptive behaviors (Cochran & Cochran, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Sehingga melalui pelaksanaan CCPT yang diberikan kepada anak slow learner untuk meningkatkan harga diri juga dapat berkontribusi pada pencapaian prestasi akademik mereka. Sebuah penelitian menunjukkan bahwa ketika anak dengan perilaku distruptif di sekolah diberikan Child Centered Therapy, dapat memberikan pengaruh pada perhatian belajar dan self-efficacy (Cochran & Cochran, 2017).…”
unclassified
“…Several studies have shown that child-centered play therapy can reduce disruptive behavior in students (Cochran & Cochran, 2017), slightly change the behavior of students with ADHD (Robinson, 2015), and be able to change academic intervention in students (Blanco, Muro, Holliman, Stickley, & Carter, 2015).…”
Section: Child-centered Play Therapymentioning
confidence: 99%